The use of counterpoint in Kurdish orchestral compositions: (Dilshad Muhammad Saeed) - misanjas, misanjas; kadir Mohammed, ary; Mohammad Mustafa, Seerwan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Kurdish music has many important transformations, including the liberation of Kurdish singing from the tarab sensuality on the one hand, the modernization of oriental music with Western classical musical instruments on the other hand, and then the enrichment of melodic and vocal writing with advanced musical sciences represented by the use of counterpoint, which led to the development of oriental music composition methods in terms of aesthetics and expression, which sought these methods, which began from the eighties (1980s) of the twentieth century to our current reality in the development of counterpoint techniques in polyphony Texture. Hence, the researchers believe that there are many experiences of Kurdish musicians in employing folkloric and folk heritage songs by treating their melodies in a contemporary musical way, i.e. by introducing polyphony (counterpoint and harmony) and diversifying in the instrumental distribution. The research aims to show the role and use of counterpoint in Kurdish orchestral compositions. It is an important part of the development and diversification of contemporary Kurdish music, in general and shows how Dilshad Mohamed Said’s counterpoint is used in his Kurdish orchestral compositions. The use of counterpoint in Kurdish orchestral compositions is an endeavor to achieve serious scientific and systematic steps in the field of artistic expression and vocal diversity, which enhances Kurdish musical culture to reach the global level.